Sistem Informasi Raport Online - alfiah, nurul (Jurnal Teknologi dan Bisnis, 2022)
Research is limited only in the process of processing student report cards which are still conventional, making it difficult for homeroom teachers to process student report cards, this system can be accessed by admins, teachers and students of Miftahul Falah Gandrungmangu Middle School, this system focuses on student report cards information. The method used is a system development life cycle with a waterfall development model. The development carried out includes analysis, design, coding and testing. In testing this system using black box testing, namely testing that is focused on the functionality side, especially on the input and output sides